Implications for breast cancer treatment from increased autotaxin production in adipose tissue after radiotherapy. Issue 9 (19th September 2017) - Meng, Guanmin; Tang, Xiaoyun; Yang, Zelei; Benesch, Matthew G. K.; Marshall, Alison; Murray, David; Hemmings, Denise G.; Wuest, Frank; McMullen, Todd P. W.; Brindley, David N.
ABSTRACT: We have previously established that adipose tissue adjacent to breast tumors becomes inflamed by tumor‐derived cytokines. This stimulates autotaxin (ATX) secretion from adipocytes, whereas breast cancer cells produce insignificant ATX. Lysophosphatidate produced by ATX promotes inflammatory cytokine secretion in a vicious inflammatory cycle, which increases tumor growth and metastasis and decreases response to chemotherapy. We hypothesized that damage to adipose tissue during radiotherapy for breast cancer should promote lysophosphatidic acid (LPA) signaling and further inflammatory signaling, which could potentially protect cancer cells from subsequent fractions of radiation therapy. To test this hypothesis, we exposed rat and human adipose tissue to radiation doses (0.25–5 Gy) that were expected during radiotherapy. This exposure increased mRNA levels for ATX, cyclooxygenase‐2, IL‐1β, IL‐6, IL‐10, TNF‐α, and LPA1 and LPA2 receptors by 1.8‐ to 5.1‐fold after 4 to 48 h. There were also 1.5‐ to 2.5‐fold increases in the secretion of ATX and 14 inflammatory mediators after irradiating at 1 Gy. Inhibition of the radiation‐induced activation of NF‐κB, cyclooxygenase‐2, poly (ADP‐ribose) polymerase‐1, or ataxia telangiectasia and Rad3‐related protein blocked inflammatory responses to γ‐radiation. Consequently, collateral damage to adipose tissue during radiotherapy could establish a comprehensive wound‐healing response that involves increased signaling by LPA, cyclooxygenase‐2, and other inflammatory mediators that could decrease the efficacy of further radiotherapy or chemotherapy.—Meng, G., Tang, X., Yang, Z., Benesch, M. G. K., Marshall, A., Murray, D., Hemmings, D. G., Wuest, F., McMullen, T. P. W., Brindley, D. N. Implications for breast cancer treatment from increased autotaxin production in adipose tissue after radiotherapy. FASEB J. 31, 4064–4077 (2017). www.fasebj.org —Meng, Guanmin, Tang, Xiaoyun, Yang, Zelei, Benesch, Matthew G. K., Marshall, Alison, Murray, David, Hemmings, Denise G., Wuest, Frank, McMullen, Todd P. W., Brindley, David N., Implications for breast cancer treatment from increased autotaxin production in adipose tissue after radiotherapy. FASEB J. 31, 4064–4077 (2017)